Bij het 25-jarig jubileum. Receptie in het Volksgebouw. Plaats personen op achterzijde - Geijtenbeek, Joh. (1925)
Bij het 25-jarig jubileum. Receptie in het Volksgebouw. Plaats personen op achterzijde.